Aplicação dirigida de herbicidas em pré e pós-corte para controle de brotações de eucalipto - William Gomes Montes (2019)
After eucalyptus trees harvesting there are emission of new sprouts that develop on the remaining stumps. These sprouts can affect the development of the seedlings posteriorly implanted. In this case it is common to use herbicides pulverization on the eucalyptus coppice before the planting reform to control the unwanted sprouts, however, usually are necessary many control operations due to the sprouts high vigor and the inadequate use of the application technologies. Therefore, two studies were developed in Eucalyptus urophylla x E. grandis plantings to assess the efficiency of different application methods on the eucalyptuss coppice control. In the first study there were developed two experiments, which consisted on the application of glyphosate or imazapyr doses, where both herbicides were applied using the post-harvest application method. Both experiments were imposed with 5 replicates and 5 treatments, equivalents to 5 glyphosates doses (0; 0,84; 1,67; 2,50; e 3,34 L e.a. ha-1) for the first experiment and 5 imazapyrs doses (0; 0,028; 0,083; 0,140; e 0,195 L i.a. ha-1) for the second experiment. The herbicides spraying was carried out upon the eucalypt cut stump surface between 42 and 48 hours after eucalypts trees harvesting. In the second study the experiment was imposed with 7 treatments and 4 replicates. The treatments were equivalents to a control treatment, without herbicide application, besides the application of glyphosate doses (1,08; 1,44; e 1,80 mL e.a. per tree) and imazapyr doses (0,075; 0,125; e 0,175 mL i.a. per tree) using the pre-harvesting application method, which consisted of the directed spraying of the herbicides on incisions carried out on the stem of the trees before harvesting. In both studies we have carried out assessments about the number of sprouts per stump, number of stump with presence of coppice, height and control efficiency of the coppice. In the first study, where the herbicide was applied using the post-harvest method, it was observed that the application of both glyphosate and imazapyr promoted high reduction of the coppices development and vigor. The coppice from stumps which there were not herbicide spraying showed medium values next to 8,0 kg of biomass and 3,0 m of height. On the other hand, the application of the increasing doses of glyphosate and imazapyr promoted high reduction in the coppices height and biomass values. The highest doses of glyphosate applied have promoted values highest than 90% of control efficiency, which led a satisfactory control level that would not demand new control operations. In the second study, where the herbicide was applied pre-harvesting, it was observed that the glyphosate spraying promoted reduction of the coppices development and vigor, although it was observed the development of coppice in at least 80% of the assessed stumps. The application of 3,0 mL of glyphosate promoted values next to 80% of control efficiency. However, it was observed that, probably, would be necessary new control operations as the control efficiency levels were not so satisfactory. The application of imazapyr presented low efficiency levels which was observed values less than 25% of control efficiency. In is concluded that the post-harvest control method, from the directed application of glyphosate, presents potential use in the control of eucalypt shoots, after the necessary adaption to make operational this activity. Additionally, the pre-harvest control method, from the directed application of glyphosate, reduces the development and vigor of eucalyptus shoots, but demands new control operations to reach satisfactory levels of control.